Upwelling Solution Prototype Using Wireless Sensor Network - Novian Anggis Suwastika; Sidik Prabowo; Bayu Erfianto (School of Computing, Telkom University, 2016)
One of the problems in the freshwater fisheries sector is the phenomenon of upwelling can occur anytime without warning signs, especially in lakes and lake. This problem causes a failed harvest and fish farming business owners suffered a great loss due to the death of fish in large numbers. Upwelling caused by toxic substances results increased nitrification from fish feces and remaining fish feed deposited at the bottom of the Lake and rises to the surface quickly. Ammonia (NH3) in the form of ionized causing no fish that are on the surface of the Lake is not enough oxygen to meet the needs of hemoglobin, so cannot bind oxygen or lack of dissolved oxygen (DO). The condition causes the death of the fish very much. This research built a monitoring system to monitor the condition of the temperature at the surface and at the underwater of the lake and to monitor DO levels to check the possibility of upwelling. Temperature sensor and DO sensor connect with microcontroller and . The results of experiment system on the area fish farms (karamba) and not the area fish farms, obtained the test results are accurate and real time.